A systems approach to small group interaction - Tubbs, Stewart L. , 1943- (McGraw-Hill, 2012)
"The only book that integrates all important small group communication topics into a single comprehensive conceptual model, this text pioneered the systems approach for the group communication course. Each chapter begins with a brief preview, followed by a glossary of terms and a real life case study. The text material in each chapter is followed by several experiential exercises for skill development and two original readings"